The Influence of Sustainable Development on Stock Risk and Volatility in Thailand’s Stock Exchange during the COVID-19 Pandemic - Laokulrach, Marisa (Asian Economic and Financial Review, 2022)
The COVID-19 pandemic has severely impacted most businesses worldwide. Sustainability management by involving Environmental, Social, and Governance (ESG) criteria is increasingly a focus of business stakeholders. This study explores the return and risk performance of 98 companies listed in the Thailand Sustainability Investment (THSI) strategy that adopted ESG measures during the COVID-19 outbreak. The regression analysis is also applied to examine the impacts of ESG pillar scores on stock returns from 2015–2021. The empirical results support the positive impact of ESG adoption to stock performance, even during the risks brought by the pandemic. Environmental and governance pillars have a statistically positive affect on stock returns, while the social pillar scores have no impact on return generating. The findings confirm the importance of sustainable development as the center of business’s strategies to cope with emerging risk and to generate better stock performance.